Shaping a universally broad antibody response to influenza amidst a variable immunoglobulin landscape. (August 2018) - Andrews, Sarah F; McDermott, Adrian B
Highlights: Conserved regions of hemagglutinin (HA) are targets for universal influenza vaccines. The immunoglobulin (Ig) response to HA is overall very diverse. Commonalities in the Ig response to HA can also be observed between individuals. Convergent Igs often target the conserved HA stem. Ig convergence can inform atomic level structural design of future HA immunogens. Abstract : One hundred years ago, the 1918 H1N1 Pandemic killed 20 million people worldwide. Despite the introduction of a worldwide surveillance system, large-scale production of influenza vaccines coupled with annual vaccination schemes, influenza remains a major public health concern. Prevention of influenza on a population basis requires intimate knowledge of the interplay between the virus' ability to escape the immune response and persistent recall and regeneration of the antibody response. Here we will briefly outline the nature of the antibody response, focusing on the response to intransigent regions of the hemagglutinin (HA) and speculate on the how this data may be used to inform and ultimately develop a universal influenza vaccine.